THE INCIDENCE OF DENTAL CARIES IN 7TH GRADE STUDENTS IN REMBANG, CENTRAL JAVA - Putu Ayu Widyary Dewanti; Retno Adriyani (Universitas Airlangga, 2020)
Background: Dental caries in children is a common multifactorial dental health problem. There are some important risk factors in the incidence of dental caries in children. Purpose: The aim of this study was to determine the incidence of dental caries and the relationship between risk factors and dental caries in 7th grade students in Rembang, Central Java. Method: An observational research design was applied, through the use of a cross-sectional study. The study population was 574, with a total sample of 75 respondents. The research sample was determined using a random sampling method. The locations of this research are SMPN 1 Lasem and SMPN 2 Rembang, Rembang, Central Java. This study was conducted between May and August 2018. Data collection techniques included dental examination for dental caries and a questionnaire to determine the risk factors. Analysis of the study was conducted via a chi-square statistical test. Results: Of the respondents, 46.67% had active caries. There was a relationship between a history of caries and a current caries incidence (p = 0.01) and between the time of toothbrushing and caries incidence in grade 7 junior high school students in Rembang Regency, Central Java (p = 0.01). Conclusion: A previous history of caries and the time of toothbrushing have a relationship with the incidence of dental caries in 7th grade junior high school students in Rembang Regency, Central Java.